Biomedical application of OrbiSIMS in cancer: identification of anti-cancer agents and metabolite profiles - Lu, Yonghui (2023)
Small molecule targeted therapies, which have been widely adopted in cancer treatments, deliver drugs directly to specific targets. Therapeutic efficacy is achieved once the target attains the necessary drug concentration. In the pursuit of novel drug candidates, the use of advanced analytical techniques is essential for enhancing our comprehension of drug concentrations at target sites and aiding in visualizing drug distributions within cells and tissues. Such advancements could potentially amplify the therapeutic efficiency of anticancer drugs. Nevertheless, many existing analytical techniques are hampered by limitations in sensitivity and visualization. This thesis introduces the superior capabilities of orbitrap secondary-ion mass spectrometry (OrbiSIMS), a solution to these challenges. OrbiSIMS facilitates the observation of an extended spectrum of endogenous metabolites, enriching biomolecular data collection. In this study, the OrbiSIMS system was used successfully for the analysis of specific biological matrices, specifically BCR-185R and MCF-7 breast cancer cells and allowed the capture of exhaustive endogenous metabolite data. Notably, the instrument enhanced the detection of lipids and amino acid species and allowed the successful identification of a broad array of metabolites. Moreover, while leveraging the imaging capabilities of OrbiSIMS, we discerned drug distribution patterns at the subcellular level. The insights gained in this study make a considerable contribution to our understanding of drug transport and have significant ramifications for the future of drug development. Although we found that OrbiSIMS possesses strong capabilities for identifying and visualising biomolecules below the cellular level, its ability to monitor drug levels under different treatment conditions and endogenous responses remains unclear. Therefore, this study evaluated the potential of OrbiSIMS to monitor drug-induced changes in endogenous metabolites and its semi-quantitative efficacy. It focussed on the anti-cancer agents Tamoxifen and Lapatinib and revealed the ability of OrbiSIMS to detect these drugs at minuscule concentrations. The instrument detected these agents at a 2000-fold dilution and an unprecedented discovery was made: the concentration of glutamine and its TCA cycle intermediates reduces in the context of MCF-7 cell metabolism. Additionally, in our research, we noted that eight established biomarkers, specifically from the lipid families phosphocholine (PC) and phosphatidylinositol (PI), responded to different treatment conditions. This discovery demonstrates the importance of OrbiSIMS in biological monitoring and biomarker identification under different treatment scenarios. The developed OrbiSIMS workflow was applied to investigate tamoxifen-resistant breast cancer and potential treatment strategies. Using this advanced analytical technique, we examined the responses of tamoxifen-resistant MCF-7/TamR-1 cells to treatments with tamoxifen, dasatinib, or their combination. Our research indicates that leucine is a key element in tamoxifen-resistant cell growth, which supports earlier findings regarding the role of leucine in drug resistance. Remarkably, the tamoxifen- resistant MCF-7/TamR-1 cells lacked increased intracellular tamoxifen intensity, even with dasatinib, which suggests that other resistance mechanisms are occurring. This research provides unparalleled 3D chemical profiles of anti-cancer agents in cancer cells, marking a pioneering use of OrbiSIMS for such analyses. The developed OrbiSIMS system will serve as an exemplar tool for addressing and comprehending the biomedical challenges within cancer research.